Cry, the Pea-cock, A perpetual meaning and value of life - Nayak, Dr. Felix (IJRDO-Journal of Applied Science, 2015)
Anita Desai’s characters are distinguished by the qualities ofintrospection, introversion and a refusal to surrender their individual selves.What one observes is a chain reaction of one leading to the other with theemerging picture of a battered and bruised individual writhing in pain andanguish. Thus Anita Desai’s novels indicate a shift from the external to theinner world of the individual. “ A marked leaning towards such an introversionis seen in Anita Desai’s writing”. 1 Her women protagonists, strive towardsarriving at a more authentic way of life than the one which is available to them.2 They in vain long for love and communion of the spirit which they perceiveas the panaceas of the ills of the world. Their refusal to compromise andsurrender and their inability to accept the perspective of their patronsinevitably result in isolation and loneliness. Lack of faith as well as lackunderstanding drive them to indulge in a futile search for fulfillment which is amirage in the inhuman and materialistic world.